2014
DOI: 10.1007/978-3-319-03041-8_51
|View full text |Cite
|
Sign up to set email alerts
|

HOBYS Observations of Ridges and Filaments, and the Evolution of Massive Dense Cores

Abstract: International audienceHerschel large-scale observations of close-by massive star-forming regions obtained by HOBYS provide an unbiased view on the detailed cloud structure and its population of massive dense cores - excellent candidates for high-mass star precursors. Structures like the DR21 ridge, the most massive cloud structure in Cygnus X, could be formed by the merging of filaments or flows: several connected sub-filaments are resolved with Herschel. The sub-filaments are gravitationally unstable and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Studies on their formation have made significant progress over the past decades (see Hoare et al 2007;Zinnecker, & Yorke 2007;Tan et al 2014;Motte et al 2017;Schilke 2017;. Observational studies have confirmed that high-mass stars form in massive dense cores (MDCs), which are ∼0.1 pc dense entities in molecular clouds with masses of tens to hundreds of solar masses (e.g., Motte et al 2007;Beuther et al 2010;Csengeri et al 2011;Hennemann et al 2014;Tigé et al 2017;Ching et al 2018). The physical conditions of high-mass star formation (HMSF) are closely related to the formation and dynamical evolution of MDCs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on their formation have made significant progress over the past decades (see Hoare et al 2007;Zinnecker, & Yorke 2007;Tan et al 2014;Motte et al 2017;Schilke 2017;. Observational studies have confirmed that high-mass stars form in massive dense cores (MDCs), which are ∼0.1 pc dense entities in molecular clouds with masses of tens to hundreds of solar masses (e.g., Motte et al 2007;Beuther et al 2010;Csengeri et al 2011;Hennemann et al 2014;Tigé et al 2017;Ching et al 2018). The physical conditions of high-mass star formation (HMSF) are closely related to the formation and dynamical evolution of MDCs.…”
Section: Introductionmentioning
confidence: 99%
“…There is a clear spatial offset, in which the ionized gas is typically found abutting one edge of the cold molecular material. Herschel column density maps have been created and their filaments analyzed in parts of the Cygnus region covered in this paper (Hennemann et al 2012;Schneider et al 2016b,a). Hennemann et al (2012) examined the DR21 filaments, which are among the brightest filaments in the region, and they derived widths of ∼0.3 pc, which may be partially affected by spatial resolution.…”
Section: Envelopes Of Cold Molecular Filamentsmentioning
confidence: 99%
“…Herschel column density maps have been created and their filaments analyzed in parts of the Cygnus region covered in this paper (Hennemann et al 2012;Schneider et al 2016b,a). Hennemann et al (2012) examined the DR21 filaments, which are among the brightest filaments in the region, and they derived widths of ∼0.3 pc, which may be partially affected by spatial resolution. We directly compare their FIR column density maps (see also Schneider et al 2016b) with the ionized gas emission and the spines identified by DisPerSE, and that shows no spatial correlation.…”
Section: Envelopes Of Cold Molecular Filamentsmentioning
confidence: 99%
“…While diffuse clouds and Gould Belt clouds generally have simple multifractal power spectra (Robitaille et al 2019(Robitaille et al , 2020, those of highmass star-forming regions are more complex and dominated, at given scales, by large gravity potentials such as hubs and ridges (Robitaille et al, in prep.). Following the definition criteria set in HOBYS articles (e.g., Hill et al 2011;Hennemann et al 2012;Nguyen Luong et al 2013) and precursor papers (Schneider et al 2010), the central part of the central subregion of NGC 2264 qualifies as a ridge. In short, ridges are very dense, >10 5 cm −3 , ∼1 pc cloud structures actively forming clusters of intermediateto high-mass stars (Motte et al 2018).…”
Section: Mass Segregation Of Clumps and Its Relationship To Cloud Str...mentioning
confidence: 99%
“…Notably, HOBYS revealed a tight link between the density, dynamics, and clump population of the so-called ridges (Motte et al 2018). The latter are high-density filaments (n > 10 5 cm −3 over ∼5 pc 3 ) forming clusters of high-mass stars (e.g., Schneider et al 2010;Hill et al 2011;Nguyen Luong et al 2011Hennemann et al 2012;Tigé et al 2017), whereas hubs are more spherical smaller structures forming at most a couple of high-mass stars (e.g., Schneider et al 2012;Peretto et al 2013;Rivera-Ingraham et al 2013;Didelon et al 2015;Rayner et al 2017). The existence of ridges and hubs is predicted by dynamical models of cloud formation such as colliding flow or gravitationally driven gas inflows simulations (e.g., Heitsch et al 2008;Smith et al 2009;Hartmann et al 2012) and some analytical theories of filament collapse/conveyor belt (Myers 2009;Krumholz & McKee 2020).…”
Section: Introductionmentioning
confidence: 99%